2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346760
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-quality assessment from full night audio recordings of sleep apnea patients

Abstract: In this work, a novel system (method) for sleep quality analysis is proposed. Its purpose is to assist an alternative non-contact method for detecting and diagnosing sleep related disorders based on acoustic signal processing. In this work, audio signals of 145 patients with obstructive sleep apnea were recorded (more than 1000 hours) in a sleep laboratory and analyzed. The method is based on the assumption that during sleep the respiratory efforts are more periodically patterned and consistent relative to a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The first selected feature extracts the apnea events in the audio signal and calculates the average number of apneas per hour -which is actually the definition of AHI. The sleep/wake detector [15] was an essential pre-step for this feature calculation and for some others. The second selected feature calculates the variance of the snores skewness based on the energy signal -which is a measure for inter-snore homogeneity -strengthening the theory that OSA snorers tend to have a greater variance of snores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first selected feature extracts the apnea events in the audio signal and calculates the average number of apneas per hour -which is actually the definition of AHI. The sleep/wake detector [15] was an essential pre-step for this feature calculation and for some others. The second selected feature calculates the variance of the snores skewness based on the energy signal -which is a measure for inter-snore homogeneity -strengthening the theory that OSA snorers tend to have a greater variance of snores.…”
Section: Discussionmentioning
confidence: 99%
“…1. Our previously published snore detector [14] and sleep/wake detector [15] were used as the first steps of each phase. Once the snores are detected, an analysis of all snore events across the night is performed; various acoustic features are extracted and investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current sleep apnoea audio recording systems acquire the signal with a broad range of sampling rates (5 kHz [28], 20 kHz [29], 44.1 kHz [30]). OSA patients' snoring sounds present a wide range of frequency response spectra depending on the physical phenomenon causing it.…”
Section: Operating System and General Set-upmentioning
confidence: 99%
“…Moreover, several studies have found that expiratory events may hold hidden information for SDB diagnosis [9][10][11]. Thus, by using the additional expiratory information, SDB diagnosis and sleep quality assessment can be improved [12,13].…”
Section: Introductionmentioning
confidence: 98%